Max Weber’s Comparative and Historical Sociology of Law. Extending the Legal Paradigm: A Prolegomenon - Toby E. Huff (Historicka Sociologie)
The recently established Complete Collection of Max Weber’s Writings [the Max Weber Gesamtausgabe] resulted in a new orientation to Weber’s Sociology of Law, now known as the Developmental Conditions of the Law. This retitling of Weber’s work-in-progress stresses the developmental intent of Weber’s study which holds the project together. Another reading of that work suggests four different levels of legal change embedded in Weber’s text and with the possibility of outlining a research program, enhanced by more recent historical studies, that prepares the way for comparing the developmental trajectories of European, Islamic, Chinese, and Russian law in appropriate time periods. This is the first installment of such a study.